Barefoot training improves physical performance in netball players - Venter, R.; de Villers, J. E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Recent research on barefoot running has focused mainly on lower-limb and spatio-temporal kinematics, its influence on kinetics of running, as well as running economy. Little is known about the effect of barefoot training on physical performance in team athletes. The aim of this study was to determine the effect of barefoot training on speed, agility, power and single-leg stability in netball players. Methods: Twenty women netball players (age: 20±2 years) were randomly assigned to a barefoot (n=10) and a shod group (n=10). Both groups performed the same drills during 20 training sessions over a period of eight weeks. Time spent training barefoot gradually increased to 40 minutes in the final session. Speed, agility, vertical jump height and single-leg stability were measured pre- and post-intervention. Results: Players in the barefoot group showed significant improvements in agility to the left (P<0.05; ES=0.74) and the right (P<0.05; ES=0.42). A large practical significant difference was found between barefoot and shod players for 10-m speed (ES=1.01) and 20-m speed (ES=0.80). The barefoot group showed significant improvements in single-leg stability for the right leg in the anterior/posterior plane (P=0.01; ES=0.22), the medial/lateral plane (P=0.04; ES=0.27), as well as overall stability (P=0.01; ES=0.25). A small practical significant difference was found for the left leg in the medial/lateral plane (ES=0.24) and overall stability (ES=0.17). No significant differences were found between the two groups with regard to vertical jump height. Discussion: Barefoot training improved speed, agility and single-leg stability in netball players. The novelty of this study makes it difficult to compare our results with previous research. Higher step frequencies and reduced contact time during barefoot running in habitually shod runners have been reported previously (Braunstein et al., 2010; Divert et al., 2008; Smith et al., 2010). It has also been suggested that barefoot training could strengthen small muscles crossing the ankle joint (Nigg, 2009) and improve proprioceptive ability (Jenkins et al., 2011). Although we did not analyse kinematic data or assess muscle strength in this study, the abovementioned aspects associated with barefoot training could have played a role in the improved performance of the barefoot group. Future longitudinal studies could determine the effect of barefoot training on prevention of ankle injuries in netball players.eft